Eficácia de fusarium spp. No controle da murcha-de-curtobacterium do feijoeiro - Soares, Rafael Moreira; Maringoni, Antonio Carlos [UNESP] (FapUNIFESP (SciELO), 2018)
This study aimed to evaluate the inhibitory action of Fusarium oxysporum f. sp. phaseoli and Fusarium spp., in vitro, on isolates of Curtobacterium flaccumfaciens pv. flaccumfaciens (Cff) and the action of Fusarium spp. in controlling bacterial wilt in bean plants, cultivar IAC Carioca, grown in pots with substrate infested by the fungus at four concentrations. Isolates of F. oxysporum f. sp. phaseoli and Fusarium spp. grown on paper filter discs, in agar culture medium, produced metabolites that inhibited the growth of Cff isolates. However, extracts obtained by filtering the cultures of fungal isolates in liquid medium did not inhibit, in vitro, the growth of Cff isolates. The isolates of Fusarium spp. infested in the substrate, regardless of the used concentration, were not effective in controlling bacterial wilt in bean plants.
Effectiveness of fusarium spp. In controlling bacterial wilt in beans
Keywords: Biological control; Curtobacterium flaccumfaciens pv; Flaccumfaciens; Phaseolus vulgaris; Resistance induction